2016
DOI: 10.15562/bmj.v5i3.335
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Budding in Breast Carcinoma: Relation to E-Cadherin, MMP-9 Expression, and Metastasis Risk

Abstract: Background: Tumor budding is a histopathologic entity refers to small cluster of cancer cells at the invasive edge of tumor. It was assumed that tumor budding is linked to epithelial-mesenchymal transition, an early event in metastasis. Objective: This study aimed to find out the correlation of tumor budding with E-cadherin and MMP-9 expression and risk of metastasis in breast carcinoma. Method: We investigated 35 cases breast carcinoma with metastasis and 35 cases without metastasis. The number of tumor buddi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 6 publications
4
14
0
Order By: Relevance
“…In the present study, PTB did not show any significant association with age of patients, tumor size, and the overall histological grade. This finding was similar to KumarGuru et al, 16 Gujam et al, 7 and Salhia et al 6 However, Sriwidyani et al 17 observed significant association of PTB with histological grade, while Liang et al 2 found a significant association of tumor size with PTB ( Table 4 ).…”
Section: Discussionsupporting
confidence: 85%
“…In the present study, PTB did not show any significant association with age of patients, tumor size, and the overall histological grade. This finding was similar to KumarGuru et al, 16 Gujam et al, 7 and Salhia et al 6 However, Sriwidyani et al 17 observed significant association of PTB with histological grade, while Liang et al 2 found a significant association of tumor size with PTB ( Table 4 ).…”
Section: Discussionsupporting
confidence: 85%
“…The results of this study are in line with research conducted by Sriwidayani et al in 2016, where they found LVI as much as 75.71%. 49 Whereas, in research conducted by Renuka et al in 2019 found LVI as much as 74%. 54 After statistical test analysis, a significant association was found between the tumor budding index and LVI in this study.…”
Section: Discussionmentioning
confidence: 92%
“…52 Sriwidyani et al in 2016 found that the average age of patients aged 48.6 years with an age range in his study of 23-74 years. 49 Kumarguru et al in 2020 found that the average age of patients is 53.14 years, with an age range of 24-77 years. 48 This study found that the age of breast carcinoma sufferers is at an advanced age that occurs in women over 50 years.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Breast cancer treatment intricately hinges on the evaluation of predictive markers and pathological insights, forming the foundation for patient-centered decisions and therapeutic strategies. Particularly within the context of early-stage breast cancer, where tailored systemic interventions mandate personalized considerations, three cardinal prognostic factors take precedence in routine clinical practice: lymph node status, tumor dimensions, and histological grade [28][29][30]. Notably, the Histological Grade (HG) of the tumor emerges as a paramount anatomical attribute.…”
Section: Introductionmentioning
confidence: 99%